Implementing Photovoice in School-based Evaluations: Navigating Challenges and Leveraging Benefits - Mostafa Hanafy; Melissa Goodnight; Valerie O'Brien (Journal of MultiDisciplinary Evaluation)
This article explores the use of photovoice as an evaluation method in a high school summer bridge program (the Innovators program). Photovoice is a participatory research method where participants take photographs and share narratives in response to prompts that solicit their perspectives and experiences. With the goal of promoting critical dialogue between participants, photovoice method leverages the power of emic knowledge and visual representation to influence programmatic change. We explain how photovoice was implemented in a K-12 mixed methods evaluation and the practical and ethical considerations that evaluators must weigh. Findings indicate that photovoice not only enhances participant engagement but also serves as a valuable tool for program evaluation, yielding rich, qualitative data that traditional methods may overlook. Drawing on a multi-year evaluation of the Innovators program, the article contributes to the growing literature on photovoice by examining what the method means for young participants, in addition to describing the photovoice design and implementation processes.